Syntactic Priming: Improving Senior High School Learners' Writing Proficiency - Meraflor Montajes Alojado (Philippine Association of Institutions for Research, Inc., 2019)
Syntactic priming is a tendency for a speaker or writer to repeat of a recently produced or heard in a language structure by processing and sharing the same underlying syntactic structure which serves as the intervention for the students who were having difficulties in writing specifically on coordinating conjunctions.  It would enhance the secondary students' writing proficiency in sentence construction to produce better-written outputs not only in educational context but also to the corporate world as well. This experimental research investigated the significant difference on the Grade 11 students Section Tulip before and after using syntactic priming as an intervention in writing. The researcher made use of structured test like pre-test and post-test to measure the effectiveness of syntactic priming in students' writing performances. Statistical techniques such as mean and t-test were also used. Analyzed data revealed that there was an increased on their scored mean from pre-test to post-test among thirty identified participants as poor writers. Furthermore, there was a significant difference between pre-test and post-test since the P-Value (0.000) was lesser than 0.5, the null hypothesis was rejected with 95% level of confidence based on the students' scores before and after taking the intervention which was not the same.